2019
DOI: 10.1016/j.clml.2018.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Ibrutinib Dose Adherence and Therapeutic Efficacy in Non-Hodgkin Lymphoma: A Single-Center Experience

Abstract: Background: As oral targeted agents, such as ibrutinib, become more widely used understanding the impact of suboptimal dosing on overall and progression-free survival outside of clinical trials is imperative. Methods: Data on ibrutinib discontinuation, dose reductions and treatment interruptions were collected on 170 non-Hodgkin lymphoma (NHL) and chronic lymphocytic leukemia (CLL n=115, 64%) patients treated with ibrutinib at a single institution. Ibrutinib dose adherence was calculated as the proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 14 publications
2
21
1
1
Order By: Relevance
“…1). Five papers were included in the final analysis which included one clinical trial and four realworld studies [9][10][11][12][13]. Out of the fifty-four studies excluded, thirty-nine were not relevant to ibrutinib dosage, four studies had been previously identified, two were pharmacokinetic studies, seven were phase I clinical trials, and two were not relevant to CLL (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Five papers were included in the final analysis which included one clinical trial and four realworld studies [9][10][11][12][13]. Out of the fifty-four studies excluded, thirty-nine were not relevant to ibrutinib dosage, four studies had been previously identified, two were pharmacokinetic studies, seven were phase I clinical trials, and two were not relevant to CLL (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…William et al analyzed the reasons for ibrutinib discontinuation in patients with non-Hodgkin lymphoma (NHL) and CLL [12]. We did not include this study in Table 2 given the more diverse patient population with reported data combining both CLL and NHL patients.…”
Section: Discontinuation Of Ibrutinib Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…One emerging hypothesis is that ibrutinib disrupts the molecular signaling cascades in the BM-tumor microenvironment and also reduces T-cell pseudo-exhaustion [126]. This could provide an explanation for why drugs like ibrutinib result in favorable OS in several lymphomas as compared to other single-agent drugs [127,128]. However, developing agents that can specifically target therapeutic agents into the BM and disrupt BM communication with high efficacy without producing non-specific systemic toxicity has been a challenge and is an area that needs more investigation.…”
Section: Newer Therapies Targeting Bm Microenvironmentmentioning
confidence: 99%
“…When a pharmacist is involved in follow-up and adherence management for oral TKIs in CML, adherence improves from 66% to 88% [24]. Similarly, a single-center retrospective analysis of CLL and non-Hodgkin's lymphoma patients on ibrutinib demonstrated that poor medication adherence (<80%) was associated with worse progression-free survival (PFS) in the subset of CLL patients [25]. In fact, missing just eight consecutive doses of ibrutinib is an important predictor of PFS and further highlights the need for close follow-up and continuity of care [26].…”
Section: Oral Chemotherapy Considerationsmentioning
confidence: 99%